LINGUOPEDAGOGICAL PRINCIPLES OF FOREIGN LANGUAGE EDUCATION OF FUTURE SPECIALISTS: EXPERIENCE OF EUROPE AND UKRAINE - Rusnak, Ivan; Vasylyk, Maryna (Mountain School of Ukrainian Carpaty, 2021)
Based on the analysis of scientific studies of modern researchers and the activities of higher education institutions in the countries of the European Union and Ukraine, the article substantiates the relevance and expediency of training future teachers of foreign languages on the basis of linguopedagogy. Their role in creating a favorable foreignlanguage educational space for direct communication of subjects of the learning process (teacher and students, teacher and student, student - student, student - students) and involvement of native speakers and modern pedagogical technologies in order to form skills of intercultural communication and acquisition of professional competences by applicants of education. The content of general pedagogical and linguodidactic disciplines as the basis of theoretical, practical and research training of future specialists in foreign language education at universities of Poland, the Czech Republic and Ukraine and improvement of their skills of oral and written communication in a multicultural environment is analyzed. It is stated that in this multidimensional process, based on the provisions of the European Recommendations on Language Education, each member state of the European Union takes into account national traditions and experience of teaching foreign languages, achievements in world linguopedagogy, individual requests and needs of its citizens, the presence of experienced scientific and pedagogical potential. It has been found that the study of pedagogical and linguodidactic cycles contributes to the formation of profound theoretical knowledge among future specialists, understanding the processes of development, socialization, education and training of growing European citizens, acquiring professional competencies for successful activity in the European educational and scientific space.